Transforming Elementary Literacy Education Through Digital Innovation and Fiction Comprehension Strategies - Rahma, Yeny; Handoyo, Eko; Mulyono, Sungkowo Edy; Yulianto, Arief (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study aims to analyze the utilization of Information and Communication Technology in literacy education within elementary schools and elementary students' literary comprehension of fictional texts. The study used a mixed-method design and involved 160 students and 20 teachers from eight schools, with the public elementary school of Kuningan 01 Semarang having the most significant student representation. The research found that educators frequently integrate laptops, projectors, and digital applications into literacy instruction, though limited connectivity and inadequate infrastructure regularly present implementation challenges. Similarly, an investigation of students' fiction comprehension shows that primary learners consistently display positive reading behaviors and generally demonstrate solid abilities in fundamental literary understanding tasks. The study recommends comprehensive strategies for literacy improvement through infrastructure development, teacher training, careful text selection, reading strategy integration, and reflective practices that address diverse learning needs.